Peran DPRD dalam Penyelesaian Sengketa Lahan di Padang Lawas - KHAIRUNNISA SIMBOLON (Politeia: Jurnal Ilmu Politik, 2015)
This study is a study pertaining Padang Lawas Legislature’s Role in the resolution of Land Dis-pute in Padang Lawas. It examined the role of Padang Lawas Legislature in resolving the dis-pute of the land. The study found that the Legislature of Padang Lawas had played several im-portant roles to solve the land-dispute case. Based on the available data, The Padang Lawas Parliament has received the direct aspiration from the people who live at the dispute area. Then, the legislature was actively involved on non-litigation actions such as a peace demonstra-tion. At last, the parliament was committed at litigation efforts such as legal action. Therefore, the legislature members were playing of their role according to the rules of parliament. A de-scriptive-qualitative method had been used in this study for describing the detail of the process and results. Field observation and interview were the technic for gathering the data in this study.Keywords: Legislature’s role, land dispute, conflict resolution.